Deterministic fatigue life simulation of flexible sign structures - Al Shboul, Khalid Walid Ahmad (Kansas State University, 2022)
Fatigue failure of highway sign structures has been recognized in many states due to sustained wind loading events. AASHTO specifies that the structural component should be designed for infinite life by maintaining the wind-induced stress below their constant amplitude fatigue threshold (CAFT). However, for the existing structures that are typically not designed for fatigue, it is essential to evaluate the condition of all the critical and fatigue-prone components for safety considerations. The visual inspection consumes a lot of time and effort and may not detect unnoticed fatigue cracks. A need for analytical inspection tools to examine all the critical members and connections in terms of remaining fatigue life has received growing attention to ensure public safety. The reliability of such analytical tools depends on the accuracy of wind loading models applied during the life span of the structure. A fill-interpolate-extend approach is devised to furnish wind loading data ensemble for the entire time span of analysis. This ensemble is utilized to establish a reliable synthetic wind model to generate fatigue cycle counts. A comprehensive analytical framework including structural modeling, stress extraction/processing, and fatigue damage simulation integrated to yield an affordable tool applicable to different sign structures topologies. The resulting software for non-cantilever overhead structure as well as cantilever and butterfly assemblies are successfully verified to predict real cases for fatigue damage reflecting the in-situ condition of the structures.
Keywords: Fatigue damage; Wind loading; Finite element; Cantilever structures; AASHTO; Structural analysis